Motivasi Masyarakat Melakukan Kegiatan Olahraga Rekreasi Dikala Pandemi Covid-19 di Boyolali - Fajar Widiyanti; Bambang Priyono (Universitas Negeri Semarang, 2022)
The purpose of this research is to describe and examine people's motivations, forms of sports activities and the potential of the environment that can be accessed by recreational sports players during the Covid-19 pandemic in Boyolali. Qualitative research approach with descriptive design. The focus of research on the motivation of recreational sports activities in Boyolali. Data collection techniques using observation, interviews, and documentation. The data validity technique uses data triangulation. Data analysis techniques with data reduction, data presentation, and conclusions. The results of the study 1) The motivation of the perpetrators of recreational sports activities during the covid-19 pandemic in Boyolali had intrinsic motivation and extrinsic motivation. 2) Forms of recreational sports activities: running, cycling, aerobics and pencak silat. Conclusions: 1) The most dominant motivation for recreational sports activities is intrinsic motivation, namely pleasure, satisfaction, keeping the body in shape, and not getting tired easily. 2) The most popular type of sports activity is aerobic exercise because it is fun and enjoyable. Besides that, the movements performed in aerobic exercise are easy to follow. 3) The potential of the environment is easy to reach, safe, comfortable, beautiful, available for hand washing and areas for recreational sports activities.